CHARITY IN THE PROCESS OF FORMING THE HUMANIST AXIOSPHERE OF CIVIL SOCIETY - M. M. Zhytnyk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The research characterizes the charity as part of civil society, which develops based on humanism in modern society. Methodology of the article is based on the complex direction of research in the dialectical interaction of the triad of a single, a special and a general that allowed to consider certain phenomena in development and interconnection, unity and contradiction, in particular, in the study and analysis of individual concepts. The author used the method of abstraction and induction with the purpose of imaginary departure from the nonessential properties and connections characterizing individual concepts, with simultaneous isolation of their most important features. Originality. The author for the first time in this work has designated the interrelation between methodological approaches and diverse practical versions of the development of charity and the opportunities of civil society based on the humanistic principle. The paper presents the developed and ready for use hierarchical pyramid of charity, the criteria for placing elements of which is the creation of the most favorable conditions for the practical development of human in general and his humanistic qualities in particular, which is directly correlated with the Maslow pyramid of needs. The author has introduced and explained the notion of «active charity», as an activity that comprehensively solves social problems. Conclusions. Charity, as an institutional and resource component of civic activity, acts as one of the practical ways of building a society on the humanity principles. However, not all forms of charity are equally effective. Representatives of active charity, the highest level of the hierarchical structure of charity, are financially stable, conscious individuals who directly act as practitioners of humanism and become most effective.